Heat treatment effect on microstructural evolution of cold spray additive manufacturing Ti6Al4V - Vaz, Rodolpho F.; Avila, Julian A. [UNESP]; Barriobero-Vila, Pere; Muñoz, Jairo A.; Albaladejo, Vicente; Cano, Irene Garcia (Springer Nature, 2025)
Cold spray additive manufacturing (CSAM) has great industrial potential due to its high deposition rate and the possibility of building metallic alloys and composite parts once the process is conducted in a solid state, preserving many raw materials properties. A material highly studied for CSAM is the Ti6Al4V alloy, which is used in medical implants and aeronautical structural components. It has a matrix of two phases (α + β) with different crystallography arrangements, compact hexagonal, and body-centered cubic, which can tailor the mechanical properties according to its volumetric percentage. To improve CSAM-ed material ductility and strength and homogenize its residual stress, heat treatments (HTs) have been employed. These HTs sinter the deposited particles, enhancing their cohesion and other properties. This study focuses on the effect of the HT parameters on the characteristics of CSAM-ed Ti6Al4V freeform parts. HT reduces the hardness from 385 in as-sprayed condition to around 320 HV0.3, conserving the porosity close to 4.0%, and increasing the HT temperature from 600 to 1000 °C improved the amount of phase β in the α grains boundaries. The findings of this study will provide valuable insights into the impact of HT on the mechanical properties and microstructure of CSAM-ed components, thereby aiding in the optimization of this manufacturing process for the Ti6Al4V alloy.